The effect of intermittent training on agility senior basketball players - شافع , عامر; كريداش , محمد لمين (Journal of Sport Science Technology and Physical Activities, 2025)
The purpose of this study was to examine the effect of intermittent training method on agility among senior basketball players. the study is based on the experimental method with two groups (experimental and control) each composed of 12 players. a program based on intermittent training is applied during (08) weeks at the rate of (03) times a week. Data collection is performed by the agilty T test. The test results showed that intermittent training has a positive effect on Agility